IMPLEMENTASI METODE INKUIRI PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA ISLAM AL MAARIF SINGOSARI - Wafiq Azizah; Anwar Sadullah; Dwi Fitri Wiyono (VICRATINA, 2022)
As time goes by, PAI learning is increasingly diverse. The use of the inquiry method makes students active in the learning process so that PAI learning objectives can be achieved. This research was conducted to see the implementation of the inquiry method in PAI subjects at SMA Islam Almaarif Singosari. The research methods used are qualitative research method and case study method. The data collection techniques used were interviews, observations and recordings. The analysis data  techniques are used data collection, data enrichment and inference. The results of this study are 1) the steps of learning planning at Almaarif Islamic High School in using the inquiry method, namely preparing lesson plans related to learning materials, determining learning objectives, preparing learning media that can support the material to be discussed and evaluation materials to be carried out during the learning process. 2) The steps for implementing learning using the inquiry method at SMA Islam Almaarif Singosari are the teacher explains the topics, objectives and learning outcomes in accordance with the inquiry method, the teacher asks questions related to the formulation of the problem and provides opportunities for discussion, the teacher gives conclusions from what has been conveyed . 3) Obstacles in the application of inquiry are caused by the different backgrounds of students. This means that the different students come from the pesantren and from outside the pesantren, which results in a lack of students accessing references from the internet.